2015
DOI: 10.1016/j.niox.2015.02.145
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle as an endogenous nitrate reservoir

Abstract: The nitric oxide synthase (NOS) family of enzymes form nitric oxide (NO) from arginine in the presence of oxygen. At reduced oxygen availability NO is also generated from nitrate in a two step process by bacterial and mammalian molybdopterin proteins, and also directly from nitrite by a variety of five-coordinated ferrous hemoproteins. The mammalian NO cycle also involves direct oxidation of NO to nitrite, and both NO and nitrite to nitrate by oxy-ferrous hemoproteins. The liver and blood are considered the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(137 citation statements)
references
References 45 publications
15
120
2
Order By: Relevance
“…Figures 1A and B show levels of nitrate and nitrite ions in liver, blood and skeletal muscle of sedentary and exercised Wistar rats and are very similar to our recent publication in which we reported that skeletal muscle in resting rodents have high levels of nitrate (19). To examine possible changes in these species with exercise, nitrate and nitrite levels were measured after the animals completed one exercise session which consisted of two 45 min runs on a treadmill with a 60 min rest period between runs, as described above.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Figures 1A and B show levels of nitrate and nitrite ions in liver, blood and skeletal muscle of sedentary and exercised Wistar rats and are very similar to our recent publication in which we reported that skeletal muscle in resting rodents have high levels of nitrate (19). To examine possible changes in these species with exercise, nitrate and nitrite levels were measured after the animals completed one exercise session which consisted of two 45 min runs on a treadmill with a 60 min rest period between runs, as described above.…”
Section: Resultssupporting
confidence: 85%
“…In our previous study we have shown that skeletal muscle is an endogenous nitrate reservoir, perhaps the largest one in the mammalian body (19). Presumably, nitrate stored in this tissue originates from NO formed from arginine by NOS1 and its oxidation by muscle oxymyoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations